Math virtual assistant

Calculators Topics Go Premium About Snapxam
ENGESP

Step-by-step Solution

Solve the inequality $2\left(x+1\right)-3\left(x-2\right)\leq x+6$

Go
1
2
3
4
5
6
7
8
9
0
x
y
(◻)
◻/◻
÷
2

e
π
ln
log
log
lim
d/dx
Dx
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Step-by-step explanation

Problem to solve:

${2\left(x+1\right)-3\left(x-2\right)}\leq {x+6}$

Answer

No steps currently available for this problem.
${2\left(x+1\right)-3\left(x-2\right)}\leq {x+6}$

Main topic:

Trigonometric Equations

Time to solve it:

~ 1.86 seconds